The use of small diameter nozzles in temperature-controlled hemp oil extraction allows high oil yields and good quality residual hemp cake feed - Sannino, Maura; Vastolo, Alessandro; Faugno, Salvatore; Masucci, Felicia; Di Francia, Antonio; Sarubbi, Fiorella; Pelosi, Maria Eleonora; Kiatti, Dieu donnè; Serrapica, Francesco (Frontiers in Veterinary Science, 2024)
The use of two nozzle diameters (6 and 8 mm) in a cold (50 °C) hemp seed oil extraction process was evaluated in terms of extraction efficiency, and chemical composition and in vitro fermentation characteristics of the residual cake. Seeds of the varieties Futura 75 and Uso 31 were pressed using a mechanical press with a cooling device. Five pressings were carried out for each variety and nozzle size, the functional parameters of the extraction processes were recorded, and the sample (n 20) of the residual cakes (n = 20) were analyzed. The 6 mm nozzle determined a higher oil yield (+4%) with a limited increase in temperature in the pressing chamber and in the oil (on average + 3 °C compared to the 8 mm nozzle). A lower oil yield and consequently a higher fat content in the corresponding cake was observed when using the 8 mm nozzleOil yield and cake composition varied with nozzle size, with lower oil yield and higher fat content in cake using 8 mm nozzle. Despite the similar fat content, the two varieties had different oil yields and different residual cake compositions. The gas productionruminal kinetic of cakes was influenced by variety but little by nozzle size. Overall, the use of a smaller nozzle in a temperature-controlled extraction process can be a useful option to increase hemp oil yield while maintaining good fermentation characteristics of the residual cakes as ruminant feed. Overall, the use of a 6 mm nozzle in a temperature-controlled extraction process allows a higher hemp oil yield without adversely affecting the residual cake as ruminant feed.